The Influence of Electronic Word of Mouth ‘Sudut Pandang’ Bandung On TikTok to Brand Awareness - Jauza Abiyya Mirza; Ratih Hasanah Sudradjat (PT Mattawang Mediatama Solution, 2023)
The internet is growing quickly in Indonesia as well, so this month it has taken over as the primary facilitator for all parts of the emerging calendar, which has the potential to make all activities easier, the actions that transform products into halal goods, effectively utilize social media, and fabricate items are those that are now being exploited in social media. This research aims to ascertain the impact of electronic word-of-mouth on public percepsetion of the Sudut Pandang Bandung as it appears on TikTok. In this research, data were gathered quantitatively utilizing survey methodologies and questionnaire distribution